Mapping NTFP collection in Tanzania: A comparison of surveys - Marije Schaafsma (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2012)
This paper presents an analysis of Non-Timber Forest Product (NTFP) collection and income in the Eastern Arc Mountains (EAM) in Tanzania, using data of the Tanzanian National Household Budget Survey 2007. The results are compared with the analysis presented in Schaafsma et al. (2011), which is based on a pooled dataset of 7 different local surveys. For both datasets, a household production function of NTFP collection is estimated, and then transferred and aggregated across the EAM to estimate the economic value of the annual flow of NTFP benefits. Although both analyses suffer from data limitations related to the employed survey methods and valuation inaccuracies related to inexistent markets, the resulting value estimates are of a comparable order of magnitude and are also comparable to earlier NTFP valuation studies. This result is important for the validation of the results presented in Schaafsma et al. (2011) and their use in future cost-benefits analyses.
Keywords: 330; non-timber forest products; household surveys; ecosystem services; Tanzania